Metastatic cancer of unknown primary in 21 dogs. (7th January 2013) - Rossi, F.; Aresu, L.; Vignoli, M.; Buracco, P.; Bettini, G.; Ferro, S.; Gattino, F.; Ghiani, F.; Costantino, R.; Ressel, L.; Bellei, E.; Marconato, L.
Abstract The aim of this retrospective study was to describe clinical features, treatment and outcome of 21 dogs with metastatic cancer of unknown primary (MCUP), a biopsy‐proven malignancy being diagnosed at a metastatic stage, in which the anatomical origin of the primary tumour cannot be detected. All dogs underwent total‐body computed tomography. Signalment, type and duration of clinical signs, metastasis site, pathology results, treatment and outcome were recorded. Carcinoma was the most common diagnosis (57.1%), followed by sarcoma, melanoma and mast cell tumour. The median number of disease sites per dog was 2, with bones, lymph nodes, lungs and spleen being the most frequent metastatic locations. The median survival for all dogs was 30 days. Overall, a primary site was not identified in 20 (95.2%) dogs. MCUP encompasses a variety of different pathologic entities and harbours a poor prognosis.